Book reviews: “Vijay Gupta, Michael Th. Rassias,” Moments of Linear Positive Operators and Approximation, Springer, 2019, viii + 96 p., ISBN 978-3-030-19454-3; 978-3-030-19455-0 (ebook). - AGRATINI, Octavian (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
In recent years the study of the linear methods of approximation became a strongly ingrained part of Approximation Theory. In the investigation of the linear positive operators the determination of their moments is extremely useful both in obtaining the convergence of the respective sequences in various function spaces and in establishing their asymptotic behavior.